Răspuns :
a)
[tex] - \frac{2}{7} - ( - \frac{5}{7} ) = \\ = - \frac{2}{7} + \frac{5}{7} = \\ = + \frac{3}{7} [/tex]
b)
[tex] - \frac{4}{3} - ( + \frac{70}{3} ) = \\ = - \frac{4}{3} - \frac{70}{3} = \\ = - \frac{74}{3} [/tex]
c)
[tex] \frac{9}{4} - ( - \frac{3}{4} ) = \\ = \frac{9}{4} + \frac{3}{4} = \\ = \frac{12}{4} [/tex]
d)
[tex] + \frac{1}{3} - ( + \frac{1}{6} ) = \\ = \frac{2}{6} - \frac{1}{6} = \\ = \frac{1}{6} [/tex]
e)
[tex] - \frac{2}{5} - ( - \frac{7}{10} ) = \\ = - \frac{4}{10} + \frac{7}{10} = \\ = + \frac{3}{10} [/tex]
f)
[tex] \frac{5}{12} - ( - \frac{1}{6} ) = \\ = \frac{5}{12} + \frac{2}{12} = \\ = \frac{7}{12} [/tex]
g)
[tex] - \frac{1}{24} - ( + \frac{9}{8} ) = \\ = - \frac{1}{24} - \frac{27}{24} = \\ = - \frac{28}{24} [/tex]
h)
[tex]4.5 - (4.5 - 3) = \\ = 4.5 - 1.5 = \\ = 3[/tex]
i)
[tex] - 7.7 - ( - 2.8) - 9 = \\ = - 7.7 + 2.8 - 9 = \\ = - 4.9 - 9 = \\ = - 13.9[/tex]